Sekolah Alam dalam Mensosialisasikan Nilai, Sikap dan Perilaku Cinta Lingkungan Terhadap Anak - Faqihana, Putri Ayyu; Shahana Nur Aini Sabila; Devita Sari; Selly Libriani; Agustina Yulianti; Taufik Muhtarom (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the efforts of Sekolah Alam in instilling environmental values in students from an early age. Using a qualitative method with a descriptive approach, this research analyzes journals and scholarly articles based on relevance and publication year. The findings indicate that Sekolah Alam implements experiential learning, direct engagement with nature, and the integration of environmental materials into the curriculum. Students are also encouraged to actively participate in maintaining cleanliness and environmental sustainability. These efforts have proven effective in enhancing ecological awareness and fostering environmentally responsible attitudes. Thus, Sekolah Alam can serve as an educational model that promotes the development of an environmentally conscious generation.